Animus Personality in Martin’s A Song of Ice and Fire: A Game of Thrones - Yurisa Yulia Yunara; M. Yuseano Kardiansyah (Universitas Teknokrat Indonesia, 2017)
This research discusses animus personality within some female major characters of Martin’s A Song of Ice and Fire: A Game of Thrones novel. It is aims to describe the implication of psychological study towards the field of literature. Those female major characters chosen are Arya Stark and Sansa Stark.. The theory applied by the writers in this research is the animus theory developed by Carl Jung. The writers use Carl Jung’s animus stage of development which consists of four stages of development that are The Man of Power, The Man of Action, The Man of Word and The Man of Meaning. The findings of the analysis show that as what Carl Jung believes that animus imprint exists in women’s characters. The difference is only about how far the animus dominated the women itself.